RANCANG BANGUN DAN MONITORING ALAT PENDETEKSI LOKASI KEBERADAAN ANAK BERBASIS ARDUINO NANO - Mawardi, Muhammad Reza; Widagda, Mikail Eko Prasetyo; Hidayati, Qory (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
Cases of missing persons are caused by natural disasters, murder, or kidnapping, including kidnapping children with various motives, such as economic motives. Today there are many cases of child abduction which are very disturbing to the community. Children who are out of parental control have increased child abductions, which can open up opportunities for individuals to commit criminal acts. The importance of the role of parents accompanying children directly or indirectly for the safety of the baby is absolute, with a monitoring tool for the location of the child's presence, parents can digitally monitor the location of the child's whereabouts and can minimize parental concerns. Monitoring using GSM and GPS modules can be the solution, a small tool, which is the right choice for parents to monitor their children's daily activities, which are mostly spent outside the home. the push button pressed by the child will send an SMS notification in the form of "I am in danger" to the parent's cellphone which has been connected to the number that has been addressed to GSM SIM 900A, then the parent can send an order in the form of a "check" so that GSM SIM 900A can send back the point the coordinates previously obtained by the Ublox Neo 6M GPS and parents can immediately review the child's location. Parents can also monitor the location of the child without having to get a notification that the child is in danger first.